The Challenges and Effects of Ascorbic Acid Treatment of Acute Pancreatitis: A Systematic Review and Meta-Analysis of Preclinical and Clinical Studies - Gao, Lin; Chong, Eric; Pendharkar, Sayali; Phillips, Anthony; Ke, Lu; Li, Weiqin; Windsor, John Albert (Frontiers in Nutrition, 2021)
Background: Oxidative stress has been implicated in the pathogenesis of acute pancreatitis (AP), and ascorbic acid (AA), as an important endogenous antioxidant substance, has been shown to reduce AP severity in preclinical studies. However, the effects of AA supplementation in clinical settings remain controversial. Methods: PubMed, EMBASE, MEDLINE, and SCOPUS databases were searched, and both preclinical and clinical studies were included. For clinical trials, the primary outcome was incidence of organ failure, and for preclinical studies, the primary outcome was histopathological scores of pancreatic injuries. Results: Meta-analysis of clinical trials showed that compared with controls, AA administration did not reduce the incidence of organ failure or mortality during hospitalization but was associated with significantly reduced length of hospital stay. Meta-analysis of preclinical studies showed that AA supplementation reduced pancreatic injury, demonstrated as decreased histological scores and serum amylase, lipase levels. Conclusion: AA administration has no effect on survival or organ failure in patients with AP but may reduce the length of hospital stay. However, the evidence to date remains sparse, scattered, and of suboptimal quality, making it difficult to draw any firm conclusion on the clinical benefits of AA in AP.